A clinical multi‐center registry study on digital nerve repair using a biodegradable nerve conduit of PGA with external and internal collagen scaffolding. Issue 5 (18th December 2018) - Kusuhara, Hirohisa; Hirase, Yuichi; Isogai, Noritaka; Sueyoshi, Yu
Abstract : Background: In this study, we evaluated the clinical efficacy of a biodegradable nerve conduit constructed of polyglycolic acid (PGA) tube with external and internal collagen scaffolding for digital nerve repair. Patients and methods: A multi‐center registry study was conducted in 11 locations between July 2013 and May 2016. Multiple mechanisms of injury included clean‐cut (12 patients), crush (5 patients), and avulsion (3 patients) types of injuries. These patients underwent nerve repair with a biodegradable nerve conduit, with 9 patients having a primary repair and 11 patients having delayed repair. Average nerve gap was 16.7 mm (range: 1–50 mm). An average of 13 months follow‐up (range: 12–15 months) was available including sensory assessments. Results: Improved s2PD was found with less severe injury as in clean‐cut (7.5 ± 1.5 mm), which was statistically significant in comparison to those in crush (9.8 ± 1.9 mm, P  = .0384) and in avulsion (10.7 ± 4.7 mm, P  = .0013) type injuries. A meaningful recovery (S3+ or S4) was observed in 90% of the 20 digital nerve repairs with a biodegradable nerve conduit of PGA with external and internal collagen scaffolding. Avulsion injuries had significantly lower levels of meaningful recovery (67%) in comparison to those of clean‐cut ( P  = .0291) and crush ( P  = .0486) types of injury. No adverse effects were reported postoperatively. Conclusion: These results indicate that a biodegradable nerve conduit of PGA with external and internal collagen scaffolding is suitable for digital nerve repair of short nerve gaps with high levels of sensory recovery as measured by two‐point discrimination.